Cybercrimes in social media: exploring social media users’ response and preparedness - Ahmad, Zeti Azreen; Asas, Asmawati (2023)
Cybercrime has becoming rampant and affecting people all around the globe. Regardless of age, gender or profession everyone has the potential to be victims. Malaysia is one of the most vulnerable regions of cyber-attacks in the world. This study was initiated in response to the recent surge of online scams on social media in the country. People have been fallen victims when their social media accounts were hacked or scammers impersonated as someone known to them or an organization offering a part-time job. Among others, this study examined how social media users respond to scams on social media platforms and their perceived preparedness to protect themselves from being victims. The study adopted a qualitative research approach using semi-structured interviews with active social media users. All interviewees were conducted online and transcribed verbatim. Findings of this study found that most respondents have experienced being scammed or at least received attempted scams. Respondents were not proactive in seeking information from authoritative sources but primarily informed about cybercrimes mainly from news, friends and others who shared their experience online. The study concludes that social media users lack preparedness in dealing with cybercrimes and are uncertain about the steps to take when they fall victims to scams. This research aims to shed light on social media users’ behavior in responding to cybercrimes and their preparedness in dealing with cyber threats.